The bacterial diversity associated with the gut of Gonipterus sp.n.2 fed on two different Eucalyptus hosts - Hammerbacher, Almuth (University of Pretoria, 2022)
Dissertation (MSc (Microbiology))--University of Pretoria, 2021.